Report on the Observance of Standards and Codes, Accounting and Auditing : Revision of the Diagnostic Tool Summary Note - Annex. Questions No Longer Inlcuded in the Diagnostic Tool - World Bank (World Bank, Washington, DC, 2017)
This report presents the questions no longer included in the revised diagnostic tool.